Γλωσσολογία τοπίου και ηγεμονισμός της αγγλικής γλώσσας: μελέτη περίπτωσης: η Μεσαιωνική πόλη της Ρόδου - Αντωναράκη, Δέσποινα (2022)
In our globalised world the need for a common language increased. This phenomenon appeared in the past for languages such as Aramaic, Greek, Latin, French etc. Now this language seems to be English, which is considered by many to be today’s lingua franca. That globalization has made a considerable impact on multidimensional aspects of human life including the language policies of many countries. This study examines the global influence of English in different levels, the role that English plays in European Community and in our country, especially in the Greek education system through the government’s planned language policy. It also goes over, to the existing problems instructional level, due to the way in which English is propagated. Secondly, it examines the linguistic landscape of countries such as Spain, Ireland, Japan and others. Finally, a research which took place during the summer- period of 2014, in the Medieval City of Rhodes shows the great influence of English language all over the area.